PENGARUH GENDER DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK DI WILAYAH KANTOR PELAYANAN PAJAK PRATAMA TAHUNA - Kakunsi, Erica; Pangemanan, Sifrid; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
This study aims to determine whether Gender and Education have an influence on taxpayer compliance with Tahuna prison service office. Compliance is a major issue of the application of the Self Assessment System. Taxpayers are entrusted by the Directorate General of Taxation to meet its tax obligations, Gender and Education Level is one of the factors that determine the behavior. The research method used is quantitative research using research and cross questionnaires to 51 individual taxpayers. Data were analyzed using ANOVA and the results showed that gender can not influence. With educational levels that have an effect on mandatory personal compliance. Will Gender and Education have no relationship in affect. The importance of education level in its implementation can be followed up by the DGT through ongoing socialization, tax counseling, taxation seminars and training, etc.Keywords: Gender, Education Level, and Tax Compliance